Arbitraging a Discriminatory Labor Market: Black Workers at the Ford Motor Company, 1918–1947 - Foote, Christopher L.; Whatley, Warren C.; Wright, Gavin (Journal of Labor Economics, 2003)
The 1918–47 employee records of the Ford Motor Company provide a rare opportunity to study a firm willing to hire black workers when similar firms would not. The evidence suggests that Ford did profit from discrimination elsewhere, but not by paying blacks less than whites. An apparent “wage‐equity constraint” prevailed, resulting in virtually no racial variation in wages inside Ford. An implication was that blacks quit Ford jobs less often than whites, holding working conditions constant. Arbitrage profit came from exploiting this nonwage margin, as Ford placed blacks in hot, dangerous foundry jobs where quit rates were generally high.